Crianças com transtorno do espectro autista: os desafios do cuidado e tecnologias cuidativas na ótica dos profissionais de saúde - SILVA JÚNIOR, Marco Antônio Mesquita da (Universidade Federal do Pará, 2025)
Autism Spectrum Disorder (ASD) is a behavioral syndrome with developmental, behavioral and social interaction disorders. Care technologies, used by the multidisciplinary team, are strategies that seek to promote satisfactory results in social interaction, behavior and breaking stereotypical routines. The study aims to reveal the challenges that permeate the care of health professionals who care for children with ASD and to learn about the care technologies used in the care of health professionals who care for children with ASD. This is a descriptive study with a qualitative approach, carried out between July and August 2023. 17 health professionals were interviewed. The data were analyzed from the perspective of Bardin's content analysis technique and processed by the software Interface de R pour les Analyzes Multidimensionnelles de Textes et de Questionnaires. The results of processing the Iramuteq software identified 6 classes and, through semantic grouping, three thematic categories emerged: “Techniques and strategies used in the intervention and behavioral management of children with ASD”; “Challenges in providing care to children with ASD” and “Role of the family in caring for children with ASD: Challenges, Acceptance and Overcoming”. It is concluded that it is essential to adopt multidisciplinary approaches, which integrate techniques, technologies, specialized clinical care, family support and integration into the social context, to promote comprehensive care for children with ASD.